Experiments in farmers' collectives in Eastern India and Nepal: Process, benefits, and challenges - Agarwal, B.; Leder, S.; Saikia, P.; Sudgen, Fraser; Raut, Manita; Kumar, Anoj; Ray, D. (Wiley, 2021)
Do farmers' collectives, which pool land, labour, capital, and skills to create medium‐sized production units, offer a more viable model of farming for resource‐constrained smallholders than individual family farms? A participatory action research project in Eastern India and Nepal provides notable answers. Groups of marginal and tenant farmers, catalysed by the project, evolved into four different collective models with varying levels of cooperation, gender composition, and land ownership/tenancy status. Based on 3 years of action research, this paper examines how the models evolved and their differential outcomes. All groups have gained from cultivating contiguous plots in their efficiency of labour and machine use for land preparation and irrigation, and from economies in input purchase. Several collectives of tenant farmers have also enhanced their bargaining power vis‐a‐vis an entrenched landlord class and thus been able to negotiate lower rents and refuse long‐standing feudal obligations. However, the models differ in their extent of economic gain and their ability to handle gender inequalities and conflicts over labour sharing. The paper explores the historical, regional, and cultural factors that could explain such differences across the models. It thus offers unique insights into the processes, benefits, and challenges of farmers' collectives and provides pointers for replication and further research.